Electrical and structural analysis of xPbO-(1-x)B2O3 (0.3≤ x≤ 0.9) glasses. (3rd March 2016) - Ait Hana, N.; Aride, J.; Haddad, M.; Benkhouja, K.; Sahraoui, B.; Taibi, M.
Abstract: Different xPbO–(1–x)B2 O3 glasses were prepared by conventional melting method. They were investigated by differential scanning calorimetry (DSC), Raman and IR spectroscopy. The glasse's structure and the PbO role to the formation of the borate units in the framework is investigated. The dielectric constant and dielectric loss were measured at different frequencies and as a function of the temperature. The electrical measurements carried out showed semiconductor behavior of the conductivity as a function of temperature. The activation energies (Ea) for the conduction process indicated a thermally activated hopping mechanism. The calculated Ea values are typically 0.67–2.46 eV.